Four years of climate warming facilitates an increase in fungal necromass in coastal wetland soils - Jine Wei; Chao Zhang; Dongliang Ma; Yanling Zheng; Fenfen Zhang; Xiaofei Li; Xia Liang; Hongpo Dong; Min Liu; Lijun Hou (Geoderma)
Microbial necromass is a vital component of soil organic carbon (SOC) stock and substantially influences soil carbon cycling. The responses of microbial necromass carbon (MNC) in coastal wetland soils to global climate warming and the factors influencing these responses, however, remain largely unclear. In the present study, a 4-year field warming experiment (+1.5 °C) was conducted with open-top chambers to reveal the response of MNC in coastal wetland soils to climate warming. The results showed differences in responses between fungal and bacterial necromass carbon (FNC and BNC) to climate warming in the soil depth of 0–50 cm. FNC content substantially increased by 17.2 % in the warmed soils as compared to that in the control soils (p < 0.05), whereas the content of BNC was not significantly different between the warmed and control soils (p > 0.05). These responses of MNC to 4-year climate warming were consistent irrespective of soil depth. The accumulation of MNC under climate warming conditions may result from a plentiful substrate availability and an alteration from nitrogen to phosphorus nutrient utilization by microorganisms, rather than changes in microbial community composition. Collectively, this study uncovers the feedback mechanism of MNC to climate warming in coastal wetlands, and emphasizes an accumulation of MNC in the blue carbon pool of coastal wetland ecosystems.